Light in the Heavens : Sayings of the Prophet Muhammad. - Qutbuddin, Tahera (Library of Arabic Literature Ser., 2019)
Humanitarian lessons and practical insights from the prophet of IslamThe words of Muhammad, messenger of God and prophet of Islam, have a special place in the hearts of his followers. Wielding an authority second only to the Qur'an, they are cited by scholars in a vast array of disciplines--including law, theology, metaphysics, poetry, grammar, history, and medicine--and are "ed by Muslims to one another in their daily lives. Light in the Heavens by al-Qadi al-Quda'i, a Sunni judge in the Fatimid court in Egypt, is an outstanding example of a compilation of these sayings, known as hadiths, that circulated orally and were later assembled and written down. From North Africa to India, generations have used Light in the Heavens as a teaching text for children as well as adults, and many of its 1,200 sayings are familiar to individuals of diverse denominations and ethnicities. For Muslims--who consider Muhammad's teachings the fount of wisdom and the beacon of guidance in all things, mundane and sublime--these sayings provide a direct window into the inspired vision of one of the most influential humans to have walked the Earth.